A Foreign Affair Billy Wilder's American Films - Gemünden, Gerd (Film Europa, 2008)
With six Academy Awards, four entries on the American Film Institute's list of 100 greatest American movies, and more titles on the National Historic Register of classic films deemed worthy of preservation than any other director, Billy Wilder counts as one of the most accomplished filmmakers ever to work in Hollywood. Yet how American is Billy Wilder, the Jewish émigré from Central Europe? This book underscores this complex issue, unpacking underlying contradictions where previous commentators routinely smoothed them out. Wilder emerges as an artist with roots in sensationalist journalism and the world of entertainment as well as with an awareness of literary culture and the avant-garde, features that lead to productive and often highly original confrontations between high and low.